A new post-synthetic polymerization strategy makes metal–organic frameworks more stable. Issue 17 (2nd April 2019) - Yang, Shuliang; Peng, Li; Sun, Daniel T.; Asgari, Mehrdad; Oveisi, Emad; Trukhina, Olga; Bulut, Safak; Jamali, Abbas; Queen, Wendy L.
Abstract : This work develops a new post-synthetic polymerization strategy to make various metal–organic frameworks more stable. Abstract : Metal–organic frameworks are of interest in a number of host–guest applications. However, their weak coordination bonding often leads to instability in aqueous environments, particularly at extreme pH, and hence, is a challenging topic in the field. In this work, a two-step, post-synthetic polymerization method is used to create a series of highly hydrophobic, stable MOF composites. The MOFs are first coated with thin layers of polydopamine from free-base dopamine under a mild oxygen atmosphere, which then undergoes a Michael addition to covalently graft hydrophobic molecules to the external MOF surface. This easy, mild post-synthetic modification is shown to significantly improve the stability of a number of structurally diverse MOFs including HKUST-1 (Cu), ZIF-67 (Co), ZIF-8 (Zn), UiO-66 (Zr), Cu-TDPAT (Cu), Mg-MOF-74 (Mg) and MIL-100 (Fe) in wet, caustic (acidic and basic) environments as determined by powder X-ray diffraction and surface area measurements.